“Why You Gotta Be So Rude?”: The Transformation of Indonesian’s Taboo Words into English - Nadia Khumairo Ma'shumah; Arif Nur Syamsi; Isra Framitha Sianipar; Muhammad Rauuf Oktavian Nur (Yayasan Visi Intan Permata, 2022)
In translation practice, the quality of the translated manuscript is influenced by the translators’ competencies by bringing culture, languages, social life, and language psychology (psycholinguistics) into account. Thus, the rendering process of taboo words frequently poses problems in translation. This study aimed at probing the emergence and transformation of taboo words as the impact of the translation of Indonesian novels to English. This study used two material objects. They were an original Indonesian novel, ‘Cantik Itu Luka’ (CIL, 2020/2002 by Eka Kurniawan published by PT. Gramedia Pustaka Utama as the Source Text (ST) and its English translation entitled ‘Beauty is A Wound’ (BIAW, 2015) translated by Annie Tucker published by Pushkin Press as the Target Text (TT). In conducting this research, researchers were stepping on Slamia (2020) on taboo words classification and Ávila-Cabrera (2015) on the tension of taboo loads for detecting taboo words transformation. Meanwhile, data were generated using documentation techniques through content analysis and scrutinized using descriptive-qualitative methods. This study led to conclusions that the transformations of taboo words were manifested and reflected by toning up or increasing, toning down or decreasing, maintaining, neutralizing, as well as omitting the SL’s taboo word in the TL. Therefore, we also found through the findings that the concept of transformation is not always appropriate for translation due to the deviation of meanings and references as taboo words in the literary text were rich in aesthetic and poetic values. These findings indicate that although translators have the authority to carry out the transformation, it was not always appropriate to be used in some contexts